2010
DOI: 10.1021/ef100482n
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Alkali Metals and Phosphorus of Rapeseed Cake in Circulating Fluidized Bed Boiler Part 2: Cocombustion with Coal

Abstract: This paper is part 2 in a series of two papers describing the fate of alkali metals and phosphorus during cocombustion of rapeseed cake pellets with different fuels in a 12 MW th CFB boiler. In the first part (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 42 publications
(78 reference statements)
2
33
0
Order By: Relevance
“…Nevertheless, at elevated temperature (750°C and an ER of 0.28) the results are in line with findings reported. 34,35 The fate of N, S, and Cl bound with the feedstock is presented in the section 3.5 ( Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, at elevated temperature (750°C and an ER of 0.28) the results are in line with findings reported. 34,35 The fate of N, S, and Cl bound with the feedstock is presented in the section 3.5 ( Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal blending ratio of 40wt% lignite and 60 wt% wood for Fischer-Tropsch synthesis was also suggested. 6 Most biomass used in co-gasification processes are woody biomasses, agricultural residues and municipal wastes. However the recent use of aquatic biomass, such as algae, for energy production 17 has received attention due to the short growth cycle, high production yield, high CO 2 fixation and flexible growing conditions 18 since it can be cultivated using low-grade water and non-arable land 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in previous studies, RS was treated with wood and coal thermally and stated the total P increase during thermal treatment. 19,20 In this study, the total P in RS-150 and LM-210 was highest among the RS and LM derived hydrochars, respectively, indicating that MW-HTC enhanced the total P. For the use of hydrochars for energy application, it was important to understand the role of N because NO x could be released from the combustion, damaging the environment. 30 In this study, N contents in RS and LM derived hydrochars decreased at higher temperatures, illustrating the effective denitrification during MW-HTC.…”
Section: Coalification and Upgradation Of Rs Andmentioning
confidence: 71%
“…The RS cake, meal, and residue are typically used as energy by combustion directly or by different alternatives. Piotrowska et al studied RS cake cocombustion with wood and coal and found P and alkali metals contents enhanced after cocombustion. , At the same time, RS residues have been studied for their potential use for amendment and fertilization of the soil. Choi et al studied the RS as a manure amendment for checking soil features and its effect on rice yield …”
Section: Introductionmentioning
confidence: 99%